Human rights NGOs in East Africa : political and normative tensions - Mutua, Makau (Pennsylvania studies in human rights., 2009)
Critically explores the anatomy of the human rights movement in East Africa, examining its origins, challenges, and emergent themes in the context of political transitions in the region. In particular, the book seeks to understand the political and normative challenges that face this young but vibrant civil society in the vortex of globalization.